Chemical and Bioactive Quality Traits During Fruit Ripening in Eggplant (S-melon gena L.) and Allied Species - Mennella, Giuseppe; Lo Scalzo, Roberto; Fibiani, Marta; D'Alessandro, Antonietta; Francese, Gianluca; Toppino, Laura; Acciarri, Nazzareno; Almeida, Adelia Emilia de [UNESP]; Rotino, Giuseppe Leonardo (Amer Chemical Soc, 2012)
A chemical and bioactive quality evaluation of phytochemicals content of 10 eggplant lines and three allied species (S. sodomaeum, S. aethiopicum and S. integrifolium) was performed. The eggplant lines were divided into the two subgroups of delphinidin-3-rutinoside (D3R) and nasunin (NAS) typologies, on the basis of the anthocyanin detected in their fruit skin. The allied species had higher glycoalkaloids content, lower soluble solids and PPO activity and absence of anthocyanins compared to the eggplant lines; S. sodomaeum stood out for high phenols content. Orthogonal contrast revealed a higher sugar content and low PPO activity in NAS- compared to D3R-typologies, whereas higher chlorogenic acid and anthocyanin contents were present in D3R-typologies. The main effect of the ripening was a decrease in phenols and in the PPO activity, not evidenced in S. sodomaeum, and an increase of glycoalkaloids in overripe fruits.A good relationship was found between superoxide anion scavenging capacity and chlorogenic acid. This study highlighted the pattern of accumulation, also evidencing variations, of several phytochemicals during the eggplant fruit development and ripening.
Keywords: glycoalkaloids; phenols; antioxidants; nasunin; delphinidin 3-rutinoside; S. aethiopicum; S. integrifolium; S. sodomaeum